Pengaruh Kepemimpinan Kepala Sekolah dan Lingkungan Kerja terhadap Kinerja Guru SD di Majalaya Karawang - Alin Hermawan; Bambang Ismaya; Abduloh Abduloh; Saepul Ma’mun; Endi Rochaendi (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study aims to analyze the influence of principals’ leadership styles and work environment on the performance of public elementary school teachers in Majalaya District, Karawang Regency, both partially and simultaneously. A quantitative approach was employed using a survey method and multiple linear regression analysis. The sample consisted of 92 teachers selected through proportional random sampling. Data were collected using a closed-ended Likert-scale questionnaire that had been tested for validity and reliability. Descriptive analysis showed that the principal’s leadership style and teacher performance were rated as "very good," while the work environment was categorized as "good." Simultaneous regression analysis revealed that both independent variables significantly influenced teacher performance, with a coefficient of determination (R²) of 0.691, indicating that 69.1% of the variance in teacher performance could be explained by leadership style and work environment. Partially, the work environment had the most dominant influence. These findings reinforce theories of organizational behavior and human resource management, emphasizing the importance of effective leadership and a supportive work environment in enhancing professional teacher performance. This study contributes both theoretically and practically to the development of adaptive, transformative, and contextual educational management strategies at the elementary school level.